ANALISA LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PT. KALBE FARMA, TBK (PERIODE 2018-2020) - Putri Puspita Dewi; Dwi Koerniawati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
The purpose of this study was to determine the financial performance of PT. Kalbe Farma, Tbk in 2018 to 2020 in terms of liquidity, solvency and profitability ratios. The theoretical basis used is financial performance. The analysis tool in this study uses a liquidity ratio which includes the current ratio and quick ratio, the solvency ratio includes the debt to assets ratio and debt to equity ratio and the probability ratio which includes return on assets and return on equity. The method used is a quantitative method which data is then obtained from the financial statements of the company PT. Kalbe Farma, Tbk and collect information from several sources such as journals. The results of this study in terms of liquidity ratios based on the current ratio and quick ratio variables in 2018, 2019 and 2020 are still not stable, but the company's assets and capital can still cover the company's debt. then seen from the solvency ratio based on the debt asset ratio and debt equity ratio variables in 2018, 2019 and 2020 the results were not good because the company in managing its assets was mostly financed by creditors than from company assets or capital. In terms of profitability ratios based on the return on assets and return on equity variables in 2018, 2019, and 2020 the results are also not good because the company's profits are less than the maximum each year or often experience a decline, as well as the company's assets and capital needs that are invested.